1994
DOI: 10.1902/jop.1994.65.8.755
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Report on a Method for Studying the Permeability of Expanded Polytetrafluoroethylene Membrane to Bacteria In Vitro: A Scanning Electron Microscopic and Histological Study

Abstract: The technique of guided tissue regeneration using expanded polytetrafluoroethylene (ePTFE) membranes has been shown to be effective in implant dentistry (bony defects, extremely thin alveolar ridges, and implants placed in fresh extraction sockets). One of the drawbacks associated with the use of membranes is their premature exposure with consequent bacterial contamination. The aim of this study was to examine the possibility that oral bacteria migrate through the occlusive portion of ePTFE membranes and to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 13 publications
1
65
0
1
Order By: Relevance
“…Complete penetration was found in all specimens in three to four weeks, and the authors recommended that prematurely exposed membranes be removed immediately to "prevent bacterial infection of the underlying regenerating tissues". Another study by Simion et al (1994b) also reported a small number of leukocytes on non-exposed e-PTFE membranes free of bacteria and a high number of bacteria on exposed sites with a corresponding reduction in bone regeneration. Consideration has been given to the application of an antibiotic such as metronidazole gel to the e-PTFE membrane on the day of insertion Sander et al, 1994).…”
Section: (D) Gbr Used In Implantologymentioning
confidence: 84%
“…Complete penetration was found in all specimens in three to four weeks, and the authors recommended that prematurely exposed membranes be removed immediately to "prevent bacterial infection of the underlying regenerating tissues". Another study by Simion et al (1994b) also reported a small number of leukocytes on non-exposed e-PTFE membranes free of bacteria and a high number of bacteria on exposed sites with a corresponding reduction in bone regeneration. Consideration has been given to the application of an antibiotic such as metronidazole gel to the e-PTFE membrane on the day of insertion Sander et al, 1994).…”
Section: (D) Gbr Used In Implantologymentioning
confidence: 84%
“…Other possible reasons for the reduced amount of bone formation are contamination of the membrane with oral microflora caused by an open wound. [25][26][27][28] More rapid resorption of bone grafting materials in areas of membrane exposure has also been reported. Jovanovic et al 29 examined 11 patients with dehiscence defects on the facial aspect of 19 threaded implants.…”
Section: Primary Closurementioning
confidence: 99%
“…Additionally, membrane exposure may necessitate premature removal, resulting in less than optimal results. 10 It would be desirable therefore, to use a resorbable membrane , but maintains its barrier function for as long as possible. Resorbable membranes with a rapid resorption profile may not exclude the connective tissue long enough for bone to completely fill the defect.…”
Section: Discussionmentioning
confidence: 99%